ANALISIS PENGARUH PDB UMKM, INVESTASI UMKM, DAN UPAH MINIMUM RATA-RATA NASIONAL TERHADAP PENYERAPAN TENAGA KERJA SEKTOR UMKM INDONESIA TAHUN 2006-2017 - RIAMA DUMAITA SIMANJUNTAK; CHAIRUL SA'RONI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The purpose of research are to knoweffect of the gross domestic product of UMKM, investment of UMKM, and the minimum wage national average against the absorption of labor in the UMKM sector, and find out the most dominant variable affect the absorption of labor in the UMKM sector. Tool analysisin this research is multiple linear regression analysis and program application to analyzed data in this research is eviews version 9.            The results showed the GDP of UMKM, Investment of UMKM, and the minimum wage national average simultaneously have significant effect on the absorption of labor in the UMKM sector. By partially, GDP of UMKM and minimum wage national average have significant effect and investment of UMKM has no significant effect on the absroption of labour in the UMKM sector.The most dominant is GDP of UMKM.Key words: Labor, GDP of UMKM, Investment of UMKM, The minimum wage national average, Indonesian.